Appraising the uptake and use of recommendations for a common outcome data set for clinical trials: a case study in fall injury prevention. Issue 1 (December 2016) - Copsey, Bethan; Hopewell, Sally; Becker, Clemens; Cameron, Ian; Lamb, Sarah
Abstract Background Many researchers and professional bodies are seeking consensus for core outcomes for clinical trials. The Prevention of Falls Network Europe (ProFaNE) developed a common outcome data set for fall injury prevention trials 10 years ago. This study assesses the impact of these recommendations. Methods A systematic search (up to 16 January 2015) was performed using Web of Science, Scopus and PubMed for articles citing the ProFaNE recommendations. Randomised trials on fall prevention in older people were selected for further analysis. Data were extracted on study characteristics and adherence to the key domains recommended by the ProFaNE consensus: falls, fall injury, physical activity, psychological consequences and health-related quality of life. Details of non-recommended outcome measures used were also recorded. Results The ProFaNE recommendations were cited in a total of 464 published articles, of which 34 were randomised trials on fall prevention in older people. Only one study (3 %) reported on all core domains. Most of the trials reported on falls (n  = 32/34, 94 %) as a core outcome measure. Most of the recommendations within the falls domain were well-followed. Around half of the trials reported on fall-related injury (n  = 16/34, 47 %). However, none reported the number of radiologically confirmed peripheral fracture events, which is the recommended outcome measure for injury. The other key domains (quality of life, physical activity and psychological consequences) were less frequently reported on, with a lack of consistency in the outcome measures used. Conclusions The ProFaNE recommendations had a limited effect on standardising the reporting of outcomes in randomised trials on fall injury prevention in older people during the search period. Authors of consensus guidelines should consider maximising buy-in by including a diversity of geographic areas and academic disciplines at the development stage and using a solid dissemination strategy.